Supernovae from stellar mergers and accretors of binary mass transfer: Implications for Type IIP, 1987A-like and interacting supernovae - Schneider, Fabian; Laplace, Eva; Podsiadlowski, Philipp (Astronomy and astrophysics, 2025)
As most massive stars are born in binary and other multiple-star systems, many are expected to exchange mass with a companion star or merge with it during their lives. This means that most supernovae (SNe) are from such binary products. Here, we focus on hydrogen-rich Type II SNe from accretors of binary mass transfer and stellar mergers, and compare them to those from single stars. We computed various SN properties such as the explosion energies, nickel yields, and neutron star (NS) kick velocities, but also consider NS masses. We find tight correlations between these parameters and various summary variables of the pre-SN core structures of stars, such as the central specific entropy, core compactness, and iron core mass. However, there is no obvious relation between these explosion properties and the evolutionary history of the pre-SN stars (i.e. single stars versus binary mass accretors and stellar mergers). We find linear relations between the nickel mass and the SN explosion energy and the NS remnant mass, and give the reasons for such relations in our models. In principle, these relations allow us to determine SN explosion energies and NS masses from nickel masses, e.g. inferred from the tail of SN light curves. We further group our models into progenitors of SNe IIP, SN 1987A-like, and interacting SNe, predict their SN and SN-progenitor properties, and compare these to observations. Overall, there is good agreement, but we also highlight some tension. Accretors of binary mass transfer and stellar mergers naturally produce SNe IIP with long plateau durations from progenitors with relatively small CO-core but large envelope masses that could explain SNe such as SN 2015ba. Our models give rise to tight relations between the plateau luminosity and the nickel mass as well as the SN ejecta velocity as inferred observationally for SNe IIP. We speculate that cool and red supergiants at log L/L⊙ ≥ 5.5 encounter enhanced mass loss due to envelope instabilities and that some could retain a hydrogen envelope to then explode in interacting SNe IIn. The rate of such SNe from our models seems compatible with the observed SN IIn rate. Some of our binary models explode as 106 L⊙ blue supergiants that may have encountered enhanced and/or eruptive mass loss shortly before their SNe, and could thus help us to understand interacting SNe such as SN 1961V and SN 2005gl but also superluminous Type II SNe such as SN 2010jl.
Online veröffentlicht: 26. August 2025
Gesehen am 19.02.2026